Mason, Belen Martinez (audio interview #4 of 4) - Martinez Mason, Belen (b. 9/29/1911 - d. 7/27/1991); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the final interview with Belen Martinez Mason, conducted in the living room of her modest tract home in Rosemead. She remained open and relaxed throughout the interview and seemed to enjoy the process a great deal. 2/17/1981